ANALISIS KESALAHAN EJAAN BAHASA INDONESIA PADA SPANDUK IKLAN DI NAMLEA KABUPATEN BURU DAN IMPLEMENTASINYA DALAM PENGAJARAN BAHASA INDONESIA KHUSUSNYA PADA ASPEK KETERAMPILAN MENULIS (Lembaga Pengembangan Kinerja Dosen, 2022)
This research aims to describe capital letter errors, word writing errors and errors in using punctuation marks on advertising banners in the city of Namlea, Buru Regency. The data used in this research is the writing on banners in the city of Namlea, Buru Regency. The instruments in this research are the researchers' own research and research. using tools in the form of General Guidelines for Indonesian Spelling (PUEBI) and the Big Indonesian Dictionary (KBBI). Data collection techniques in this research are observation and documentation techniques, then identification of descriptions and classification of data based on errors contained in advertising banners in Namlea City using using a qualitative descriptive approach. Analysis results from the data collected contained Indonesian spelling errors on advertising banners in Namlea, Buruse Regency, consisting of 51 cases of errors. Errors in the use of capital letters, errors in writing words, and errors in the use of punctuation marks. Furthermore, the implementation of banners on every road plays an important role in supporting the success of the learning process in schools. Because banners are indirect communication for each person and student, then it is a one-way communication that we seem to be aware of, therefore if the writing on the advertising banner that we see or read changes the letters in each word then this will affect knowledge. for everyone who reads it.